The Young Women's Health CoOp in Cape Town, South Africa: Study protocol for a cluster-randomised trial for adolescent women at risk for HIV - Wechsberg, W.M.; Browne, F.A.; Carney, T.; Myers-Franchi, Bronwyn; Minnis, A.; MacDonald, R.; Ndirangu, J.W.; Turner, L.B.; Howard, B.N.; Rodman, N. (BMC, 2018)
Background: South Africa remains the global epicentre of HIV infection, and adolescent women have the highest incidence of HIV in the country. South Africa also has high rates of alcohol and other drug (AOD) use, violence, and gender inequality. Violence converges with AOD use, gender inequities and other disparities, such as poverty, to increase sexual risk and poor educational attainment for adolescent women. This study seeks to test the efficacy of peer recruitment and cofacilitation of the Young Women's Health CoOp (YWHC), a comprehensive gender-focused intervention to reduce HIV risk behaviours and increase the uptake of HIV counselling and testing (HCT) among out-of-school, adolescent women who use AODs. The YWHC is facilitated by local research staff and supported by peers.